Frequency and Antimicrobial Sensitivity Spectrum of Bacterial Pathogens Responsible for Neonatal Sepsisat Sir Ganga Raam Hospital, Lahore - JAVERIA GUL, JAVARIA ABDUL JABBAR, KOKAB JABEEN, (Journal of Fatima Jinnah Medical University, 2018)
Background: Neonatal sepsis is a life threatening problem in neonates which is one of the major contributor of neonatal mortality especially in developing countries.The aim of our study is to enlist the organisms predominantly responsible for neonatal sepsis in our hospital and todeterminetheirantimicrobialspectrumofsensitivity. Surveillance should be conducted shortly apart (every 3-6 months) to update the causative organisms and their sensitivity spectrum in particular localities.The administration of organism specific antibiotics will be helpful in decreasing the number of multidrug resistant strains which are spreading due to the administration of broad spectrum antibiotics, being given to patients on empirical grounds. Aims & Objective: The aim of our study is to determine the bacterial pathogens commonly responsible for neonatal sepsis in our setup and to determine their antimicrobial spectrum of sensitivity. This will help us deciding which antibiotic should be administered empirically to the patients presenting to us with neonatal sepsis, when a culture report is awaited. Study Design:Cross-sectional observational study. Setting:Microbiology Laboratory of Fatima Jinnah Medical University, Lahore. Duration of Study:1st August 2015 to 29th February 2016, (six months). Subjects and Methods: Study was conducted on342blood culturesamples. These sampleswereculturedandafter confirmingtheoffendingagentitsantimicrobialsusceptibilitypatternwasalso determined. Results:Outof342bloodculturesamplesreceived,117werepositiveforgrowth.Of117 positivecultures,37samples(32%)showgrowthofCitrobacterspecies,20(17%)ofStaphylococcus aureusand17(15%)ofKlebsiellaspecies. Conclusion:Thecommonest organism responsible for sepsis in neonates in our setup is Citrobacterspecies,secondmostcommonbeingStaphylococcusaureusandthirdoneisKlebsiella species.